PLAU1 Facilitated Proliferation, Invasion, and Metastasis via Interaction With MMP1 in Head and Neck Squamous Carcinoma - Wu, Kun; Mao, Yuan-Yuan; Han, Nan-Nan; Wu, Hanjiang; Zhang, Sheng (Frontiers in Oncology, 2021)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most common malignant neoplasm; it is associated with high morbidity and mortality. Thus, understanding the molecular mechanisms underlying its initiation and progression is critical for establishing the most appropriate treatment strategies. We found that urokinase-type plasminogen activator (PLAU1) was upregulated and associated with poor prognosis in HNSCC. Silencing of PLAU1 inhibited the proliferation, colony-formation, migration, and invasion abilities of HNSCC cells in vitro and reduced the expression of matrix metalloproteinase 1 (MMP1), whereas PLAU1 overexpression significantly enhanced the growth, the colony-formation, migration, and invasion abilities, and the xenograft tumor growth of HNSCC cells in vivo and increased the expression of MMP1. The Co-IP assay verified that PLAU1 interacted with MMP1. A positive correlation between PLAU1 and MMP1 expression was observed in HNSCC samples. si-RNAs against MMP1 reversed the aggressive effects of PLAU1 overexpression in HNSCC. Taken together, our data revealed that PLAU1 facilitated HNSCC cell proliferation, invasion, and metastasis via interaction with MMP1.